Pengaruh Good Corporate Governance (GCG), Ukuran Perusahaan, dan Pertumbuhan Penjualan terhadap Kinerja Keuangan ada PT Ace Hardware Indonesia yang Terdaftar di BEI Periode 2015-2024 - Akbarudin Akbarudin; Mohamad Safii (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study aims to analyze the effect of Good Corporate Governance (GCG), Firm Size, and Sales Growth on Financial Performance at PT Ace Hardware Indonesia Tbk listed on the Indonesia Stock Exchange (IDX) during the 2015–2024 period. Good Corporate Governance (GCG) in this study is proxied by institutional ownership, financial performance is measured using Return on Assets (ROA), firm size is measured by the natural logarithm of total assets, and sales growth is measured using the sales growth ratio. This study employed a quantitative method with a descriptive approach. The data used were secondary data in the form of annual financial statements obtained from the official websites of the IDX and the company. Data analysis techniques included descriptive statistics, classical assumption tests, multiple and simple linear regression analysis, and hypothesis testing consisting of t-test, F-test, and coefficient of determination with the assistance of SPSS version 27 software. The results of the study indicate that partially, the Good Corporate Governance (GCG) variable has a t-value of -1.526 < t-table 2.447, meaning that it has no significant effect on financial performance. The firm size variable has a t-value of -2.857 > t-table 2.447, indicating a significant negative effect on the company’s financial performance. The sales growth variable has a t-value of 1.593 < t-table 2.447, meaning that it has no significant effect on financial performance. Simultaneously, Good Corporate Governance (GCG), firm size, and sales growth have a significant effect on financial performance, with an F-value of 13.023 > F-table 4.76 and a significance value of 0.005 < 0.05. This study is expected to provide consideration for management and investors in decision-making and serve as a reference for future research in related fields.